Cofilin‐1–induced actin reorganization in stored platelets. Issue 4 (11th March 2020) - Dasgupta, Swapan K.; Thiagarajan, Perumal
Abstract : BACKGROUND: During platelet storage, there are extensive changes in cytoskeleton and phosphatidylserine exposure. The intrinsic mitochondrial pathway of apoptosis, activated in stored platelets, is a major mediator these changes. Cofilin‐1 is an effector of actin reorganization. We examined the effect of cofilin‐1 deficiency on cytoskeleton and phosphatidylserine exposure during storage and following activation of apoptosis. METHODS AND RESULTS: We assessed actin filaments by Alexa‐647‐phalloidin and phosphatidylserine exposure by fluorescein isothiocyanate–lactadherin by fluorescence microscopy. In fresh platelets, actin filaments are distributed in the subcortical region, and they do not express phosphatidylserine in the outer surface. In stored platelets, there is retraction of actin filaments from the subcortical region with increased phosphatidylserine expression. These changes are seen in 20% of platelets of 6 days old and increases further with storage. Treatment with ABT‐737, which activates the mitochondrial apoptosis, induces similar cytoskeletal changes in actin filaments with increased phosphatidylserine. Cofilin‐1 is activated in stored platelets as well as in ABT‐737 treated platelets by dephosphorylation. In cofilin‐1 deficient murine platelets actin filaments are abnormal and ABT‐737 induces less phosphatidylserine. Despite these changes in vitro, platelet survival of cofilin‐1 deficient platelets in mice was not significantly different from their wild‐type controls. CONCLUSION: These results show that cofilin‐1 plays a role in apoptosis‐induced actin rearrangement and phosphatidylserine exposure during storage. Despite the defects in platelet cytoskeleton and phosphatidylserine exposure in cofilin‐1–deficient platelets, the in vivo life span of platelets is similar to littermate controls, indicating multiple redundant pathways for the clearance of platelets in vivo.